Lima, enero de 1881: saqueo, matanza, guerra de razas y Comuna - Guzmán Palomino, Luis (2020)
The events that occurred in Lima and Callao following the disasters of San Juan and Miraflores are described: anarchy, chaos and terror, looting, killing and fighting, from the afternoon of the 15th to the early hours of January 17th, 1881, during which time «blood flowed freely» and the «communists» were blamed for causing the disturbances. Accounts by Peruvian, Chilean and other foreign observers allude to this, as well as to the significant presence of the non-politicized underclass. There was even talk of «race war». Economic losses were calculated at two million pesos and several hundred people were killed, particularly among the Chinese, whose homes and businesses were razed, and also among the underclasses, who were severely repressed by a large urban guard composed of foreign residents, which pacified the city prior to its seizure by the Chilean invaders. This is an overlooked chapter in the so-called «Lima campaign».